Investigation of sound properties of High Density Polyethylene / Styrene Butadiene Rubber polymer composites - (:unkn) unknown (JVE International, 2013)
Polymers are used in many areas today and able to produce specially with enhanced features. For this reason, Polymer Industry has developed several polymers composite. Some features of polymer composites are examined in determining areas and to improve these properties such as mechanical, thermal, electricity and morphological. One of the important features of the sound characteristics of a material that can help identifies the areas where the material is used. Provide strength and comforts of used materials are very important in transportation technologies such as rail vehicles, automotive and aircraft. In this study High Density Poly Ethylene (HDPE) with Styrene Butadiene Rubber (SBR) polymer with elastomeric composites with properties were determined of the sound. Firstly, a sound absorption material composed of blends of HDPE with SBR developed. After then HDPE/SBR composite's sound absorbing characteristics were investigated in an impedance tube, according to transfer function method. Measurements show that HDPE ratios have a significant effect on the acoustic absorption performance of the blend due to their microstructures and physical features. Furthermore, a polymer blend of High Density Poly Ethylene and Styrene Butadiene Rubber was tested in order to quantify its sound properties such as sound absorption and impedance ratio. There was sound absorption in the frequency range between 100 and 6400 where is high frequency range. All the data was filtered via MATLAB numeric analyses program. In the light of all these data, it was seen that SBR contribution leads to property of acoustics behaviors. © 2013 VIBROENGINEERING.